Ocean‐Forced Ice‐Shelf Thinning in a Synchronously Coupled Ice‐Ocean Model. Issue 2 (3rd February 2018) - Jordan, James R.; Holland, Paul R.; Goldberg, Dan; Snow, Kate; Arthern, Robert; Campin, Jean‐Michel; Heimbach, Patrick; Jenkins, Adrian
Abstract: The first fully synchronous, coupled ice shelf‐ocean model with a fixed grounding line and imposed upstream ice velocity has been developed using the MITgcm (Massachusetts Institute of Technology general circulation model). Unlike previous, asynchronous, approaches to coupled modeling our approach is fully conservative of heat, salt, and mass. Synchronous coupling is achieved by continuously updating the ice‐shelf thickness on the ocean time step. By simulating an idealized, warm‐water ice shelf we show how raising the pycnocline leads to a reduction in both ice‐shelf mass and back stress, and hence buttressing. Coupled runs show the formation of a western boundary channel in the ice‐shelf base due to increased melting on the western boundary due to Coriolis enhanced flow. Eastern boundary ice thickening is also observed. This is not the case when using a simple depth‐dependent parameterized melt, as the ice shelf has relatively thinner sides and a thicker central "bulge" for a given ice‐shelf mass. Ice‐shelf geometry arising from the parameterized melt rate tends to underestimate backstress (and therefore buttressing) for a given ice‐shelf mass due to a thinner ice shelf at the boundaries when compared to coupled model simulations. Key Points: The first synchronously coupled, fully conservative ice shelf‐ocean model has been developed Unlike a simple parameterized melt simulation, coupled runs have asymmetric ice‐shelf topography For a given ice‐shelf mass, parameterizing melt tends to underestimate ice‐shelf buttressing